2021
DOI: 10.1002/cam4.4354
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle gauge as a prognostic factor in patients with colorectal cancer

Abstract: Background Although skeletal muscle index (SMI) and radiodensity (SMD) are well‐known prognostic factors, the clinical impact of the integrated measure, known as skeletal muscle gauge (SMG), has been limited in patients with colorectal cancer (CRC). Patients and Methods A total of 727 and 268 patients with CRC at two tertiary centers were included and allocated into the training and test sets, respectively. Preoperative slice computed tomography images of the third lumbar area were evaluated for SMI and SMD. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Our study confirms that for population research assessing body composition at a single timepoint, single‐slice area measures and multi‐slice volumes are highly concordant and have similar associations with all‐cause mortality; thus, both approaches can be used interchangeably. Indeed, we replicated the known associations of lower SKM quantity 2 , 27 , 28 and radiodensity 29 , 30 , 31 , 32 , 33 , 34 with lower survival using both measurement approaches. With the routine use of CT for surveillance and surgical planning, body composition measurements can be derived for many patients and are consistently associated with a host of clinical outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…Our study confirms that for population research assessing body composition at a single timepoint, single‐slice area measures and multi‐slice volumes are highly concordant and have similar associations with all‐cause mortality; thus, both approaches can be used interchangeably. Indeed, we replicated the known associations of lower SKM quantity 2 , 27 , 28 and radiodensity 29 , 30 , 31 , 32 , 33 , 34 with lower survival using both measurement approaches. With the routine use of CT for surveillance and surgical planning, body composition measurements can be derived for many patients and are consistently associated with a host of clinical outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…In some studies, it has been shown that SMI and SMD act as independent prognostic factors in terms of survival (15)(16)(17). Recent studies have also focused on SMG obtained by the integration of SMI and SMD (8,9,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating the effect of SMG on survival in patients with CRC (8), SMG values were measured only in CT examinations obtained before treatment. It was reported the values in the diagnostic CT scans, but also the follow-up images of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia significantly affects the prognosis of patients with malignancies. It is a well-known independent risk factor for poor prognosis in malignancies ( 3 6 ). There is a 12–60% prevalence of sarcopenia in CRC patients ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%